Patients’ knowledge and perspectives on wet age-related macular degeneration and its treatment - Sushma Kandula (Dove Medical Press, 2010)
Sushma Kandula1, Jeffrey C Lamkin1, Teresa Albanese2, Deepak P Edward11Department of Ophthalmology, 2Health Service Research and Education Institute, SUMMA Health System, Akron OH, USASummary: There have been no studies examining the level of understanding age-related macular degeneration (ARMD) patients have about their disease, or their perceptions about intraocular injections as treatment. In this study, patient knowledge about ARMD risk factors was low but patients appeared more optimistic than fearful when confronted with intraocular antivascular endothelial growth factor (anti-VEGF) injections as treatment.Purpose: In recent years there has been an increase in our understanding of wet ARMD, and a dramatic shift in the treatment paradigm. However, to our knowledge, no studies have examined how much ARMD patients understand their disease, or how they feel about receiving intraocular injections as treatment. The primary objectives of this study are to identify areas in which ARMD patients may be uninformed about their disease, and to recognize specific fears or expectations that patients may have regarding treatment with intraocular anti-VEGF injections.Design: Prospective, survey-based study.Methods: This is a prospective survey-based study. An anonymous 32-item questionnaire was compiled and distributed to patients with wet ARMD who underwent at least one intraocular anti-VEGF injection. Eighty-three patients from a retina practice in a suburban setting completed the questionnaire that gauged both their knowledge of ARMD and their perspectives on its treatment. Data was analyzed using chi-square testing.Results: Seventy-eight percent of patients received most of their knowledge of ARMD from their physician. Eighty-nine percent of patients prefer to receive more information on ARMD, if needed, directly from their physician. Only 21%, 48%, 37%, 48%, and 36%, respectively, correctly identified how diet, special vitamins, high blood pressure, family history, and smoking can affect ARMD. Sixty percent felt somewhat afraid or very afraid about getting their first intraocular injection but this did not correlate with pain or discomfort during treatment (P = 0.075, P = 0.117). Eighty-nine percent were very satisfied and 11% were somewhat satisfied with the explanation their physician gave them about the injections. Eighty percent reported feeling hopeful (significantly more than any other emotion) when they were first told they needed an intraocular injection for treatment of their disease.Conclusions: Knowledge of risk factors and risk factor modification among patients with ARMD is low. Since the vast majority of ARMD patients prefer to receive information directly from their physician, patient education is crucial in improving risk factor modification and alleviating fears of treatment. With the advent of anti-VEGF agents, patients appear more hopeful of regaining vision than they are fearful of treatment with intraocular injections.Keywords: age-related macular degeneration, patient education, fear of needles, anti-VEGF, macular degeneration risk factors, macular degeneration treatment, ranibizumab